2021
DOI: 10.1021/acsami.1c18606
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Quantum Tunneling through a Graphene/Bi2Se3 Heterointerface for the Hybrid Photodetection Mechanism

Abstract: Graphene-based van der Waals heterostructures are promising building blocks for broadband photodetection because of the gapless nature of graphene. However, their performance is mostly limited by the inevitable trade-off between low dark current and photocurrent generation. Here, we demonstrate a hybrid photodetection mode based on the photogating effect coupled with the photovoltaic effect via tunable quantum tunneling through the unique graphene/Bi 2 Se 3 heteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…As we suggested earlier, the charge transport at reverse bias might be dominated by tunneling. Thus, we adopted direct tunneling (DT) and FNT models to fit the I – V curves at reverse bias. DT and FNT are expressed using the following equations ln ( I D T V 2 ) = A q 2 m 0 normalΦ normalB h 2 d ln ( 1 V ) 4 π d 2 m * normalΦ normalB h ln ( I F N T V 2 ) = ln ( A q 3 m 0 8 π h Φ B d 2 m * ) 8 π d 2 m * normalΦ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we suggested earlier, the charge transport at reverse bias might be dominated by tunneling. Thus, we adopted direct tunneling (DT) and FNT models to fit the I – V curves at reverse bias. DT and FNT are expressed using the following equations ln ( I D T V 2 ) = A q 2 m 0 normalΦ normalB h 2 d ln ( 1 V ) 4 π d 2 m * normalΦ normalB h ln ( I F N T V 2 ) = ln ( A q 3 m 0 8 π h Φ B d 2 m * ) 8 π d 2 m * normalΦ …”
Section: Resultsmentioning
confidence: 99%
“…As we suggested earlier, the charge transport at reverse bias might be dominated by tunneling. Thus, we adopted direct tunneling (DT) and FNT models to fit the I – V curves at reverse bias. DT and FNT are expressed using the following equations where A , q , m 0 , Φ B , h , d , and m *­(0.45 m 0 ) are the junction area, elementary charge, free electron mass, barrier height, Planck constant, the thickness of MoS 2 flake, and effective electron mass, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, attention has been directed toward coupling a graphene layer to the 2D surface of a three-dimensional topological insulator (3DTI). , The proximity of a 3DTI to graphene can induce sizable SOC and correspondingly spin textures in graphene, with the further possibility of inducing Dirac states with very low Fermi velocity, in which interaction effects are predicted to be greatly enhanced . Of particular relevance is the tetradymite class of 3DTIs, which comprises bismuth chalcogenides like Bi 2 Se 3 , Bi 2 Te 3 , and Bi 2 Te 2 Se (BTS), because the lattice constants of their (111) surfaces have only a small mismatch with graphene, in stark contrast to large mismatches of for the transition-metal dichalcogenides on graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the photovoltaic effect is beneficial for fast photoresponse [13] and low power operation while the photogating effect is useful for high optical gain [14]. Very recently, it has been reported that this vdW heterojunction is a very suitable platform to study new 1 Hoon Hahn Yoon, Henry A. Fernandez, Fedor Nigmatulin, Faisal Ahmed, Xiaoqi Cui, Xueyin Bai, Diao Li, Mingde Du, Harri Lipsanen, Zhipei Sun are with the Department of Electronics and Nanoengineering, Aalto University, Fi-00076 Aalto, Finland (corresponding author: Hoon Hahn Yoon, email: hoonhahn.yoon@aalto.fi) photodetection mechanisms such as switchable [15], [16], hybrid [17], [18], negative [19], [20], and anti-ambipolar [21], [22] photoresponses. Based on vdW heterojunctions, a single dominant photodetection mechanism can be switched from one to another [15], [16] for multimode optoelectronics and its logic or neuromorphic computing applications, which is readily achievable by the engineering of band alignment or bending.…”
Section: Introductionmentioning
confidence: 99%